Structured project learning model toward improved competitiveness in bidding for large construction firms - Abdul-Rahman, Hamzah; Wang, Chen; Malay, Shamini Batu (Journal of Civil Engineering and Management, 2012)
Changes and uncertainties are inevitable in the construction industry so that contractors have to find ways to improve themselves in all aspects in order to enhance their competitiveness in tendering as it determines their survival in the industry. It is believed that experiences and knowledge of past projects have the potential to improve the competitiveness of the bids submitted. This study aims to propose project learning in a structured manner as an effective approach for improvements in bidding. Through a questionnaire survey, the five most significant benefits from project learning for the betterment of bid submissions were identified, namely: “improved accuracy in pricing”, “more realistic estimates”, “better evaluation of risks involved in tendering for a project”, “less rework and repetition of mistakes”, and “faster resolution of similar problems”. Further, the five most suitable project learning methods for improvement in bidding were recommended, which included “periodic learning meeting”, “documentation learning”, “on job training”, “debriefing”, and “informal face-to-face interaction”. Accordingly, a structured learning model toward improved bidding is developed for large construction firms.